An Interannual Comparative Study on Ecosystem Carbon Exchange Characteristics in the Dinghushan Biosphere Reserve, a Dominant Subtropical Evergreen Forest Ecosystem - Njoroge, Brian; Li, Yuelin; Wei, Shimin; Meng, Ze; Liu, Shizhong; Zhang, Qianmei; Tang, Xuli; Zhang, Deqiang; Liu, Juxiu; Chu, Guowei (Frontiers in Plant Science, 2021)
Stronger ecosystem carbon sequestration potential of evergreen forests with respect to terrestrial forests in subtropical China is of great research interest. Eddy flux data helps to obtain accurate values of forest-atmosphere CO2 fluxes in order to determining ecosystem carbon exchange characteristics in a forest. The subtropical monsoon evergreen broad-leaved forest in Dinghushan is suitable for this study because, as compared to other regions on the same latitude, it has a warm and humid climate thus playing a role in the region’s carbon cycle. We hypothesized that the Dinghushan forest functions as an overall carbon sink and that its carbon sequestration capacity has been increasing over time. Our objectives were: (1) to make a comparison of net CO2 fluxes obtained using the eddy covariance technique (2) to establish the effects of various environmental factors on the net CO2 fluxes, and (3) to utilize the Michaelis–Menten type model and the physiologically based process model to track and report the ecosystem’s carbon exchange characteristics. To achieve our objectives, we used eddy covariance for ecosystem CO2 flux estimation. Seasonal trends were observed in the daily ecosystem fluxes that indicate a sensitivity to climatic factors such as air temperature, precipitation and PAR. The carbon sequestration ability showed a seasonal variation with October to December having a greater carbon sink capability of -1435 g C m−2 y−1 (48.4%) whereas April to September had a weaker carbon sink capability of -1197 g C m−2 y−1(40.4%). The measured NEE varied from -518 g C m−2 y−1 to -211 g C m−2 y−1, measured RE varied from 1142 g C m−2 y−1 to 899 g C m−2 y−1 and GPP varied from 1552 g C m−2 y−1 and 1254 g C m−2 y−1. Dinghushan forest ecosystem is a net Carbon sink, however, the carbon sequestration capacity has not increased significantly during the study period. The models in this study are suitable for studying other ecosystems across the world to help in their conservation. The Dinghushan ecosystem is an exemplary model forest in the absorption and sequestration of CO2 from the atmosphere.